UPAYA PENGEMBANGAN POTENSI WISATA BERBASIS COMMUNITY BASED TOURISM DI DESA BATU KUMBUNG KABUPATEN LOMBOK BARAT - I Nengah Darmayasa; Murianto Murianto; I Putu Gede (Journal Of Responsible Tourism, 2023)
This study discusses the development of tourism potential diversity based on community based tourism in Batu Kumbung Village, West Lombok Regency. The purpose of this study is described to describe the diversity of tourism potential and to analyze efforts to develop the diversity of tourism potential based on community based tourism in Batu Kumbung Village. This research uses interview, observation, and documentation methods and a qualitative descriptive approach. The results showed the development of the diversity of tourism potential based on community based tourism owned by Batu Kumbung Village in terms of natural tourism potential, cultural tourism potential and artificial tourism potential. Efforts to develop the diversity of tourism potential based on community based tourism in Batu Kumbung Village consist of training and promotion.